Indonesian Teachers Perspective on the Characteristics and How to Teach Science in Elementary School - Sapitri, Riska Dia; Irawan, Rizka Sofia; Assirri, Ryya Aulia (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Science education plays a critical role in shaping students' scientific literacy and attitudes. Teachers' perspectives on the nature of science (NoS) are central to how science is taught in classrooms, particularly at the elementary level. This study aims to analyse the views of elementary school teachers in Indonesia on the fundamental characteristics of science and how they implement these views in their teaching practices. Using a descriptive quantitative approach, complemented by Focus Group Discussions (FGD), data were collected from 52 teachers across diverse geographical regions, including West Nusa Tenggara, Java, and East Nusa Tenggara. The data were analysed based on four core aspects of the nature of science: science is interesting to study, science is useful in life, science continues to develop, and science is a global human endeavour. The results show that most teachers have very positive views on the first three aspects, while their understanding of the global dimension of science is categorised as good. Further analysis revealed no significant differences in teachers' views based on length of service, gender, or PPG (Teacher Professional Education) status. These findings suggest the need to enhance teachers' pedagogical competence through globally oriented training programs and contextualised science teaching approaches. This study contributes to improving the quality of science education by encouraging a more holistic and globally relevant understanding of science among primary school teachers.